Toddlers in Transition: Linear Enamel Hypoplasias in the Hadza of Tanzania. (3rd May 2017) - Ungar, P. S.; Crittenden, A. N.; Rose, J. C.
Abstract: Bioarchaeologists often use linear enamel hypoplasias (LEH) as a proxy for systemic physiological stress in prehistoric populations. Increased incidences of LEH have been observed in many cases associated with rapid social or environmental changes, such as with the Neolithic transition and agricultural intensification. Still, there have yet to be studies published of LEH incidence among living peoples in the process of transitioning from foraging to a farming economy. It is important to document LEH occurrence in living groups with known subsistence strategies to better contextualise interpretations of bioarchaeological populations. Here, we present LEH data for a sample of the Hadza of Tanzania. We compare LEH incidence and frequency on the permanent anterior teeth of individuals who spent their infancy and early childhood (i) in the bush consuming wild foods; (ii) in the village with a weaning diet dominated by domestic cereals; and (iii) transitory, dividing their time between the bush and village. Our results demonstrate that Hadza living in the bush during the period of tooth formation less frequently have LEH on these teeth, and have fewer of them on average, than do villagers. This is particularly so for the comparison of men. The transient group is intermediate in LEH incidence, although not significantly different from the bush and village samples. A lower LEH frequency in the bush Hadza is consistent with a diet that meets nutrient requirements of tooth formation, but higher incidence in the village sample suggests interruption of enamel secretion, most likely due to malnutrition. Such studies provide valuable context with which to interpret and understand bioarchaeological evidence, and to track effects of sedentisation on the biology of modern foragers. Copyright © 2017 John Wiley & Sons, Ltd.